2006
DOI: 10.1007/s10495-006-9037-8
|View full text |Cite
|
Sign up to set email alerts
|

Postconditioning attenuates cardiomyocyte apoptosis via inhibition of JNK and p38 mitogen-activated protein kinase signaling pathways

Abstract: A sequence of intermittent interruptions of oxygen supply (i.e., postconditioning, Postcon) at reoxygenation reduces oxidant-induced cardiomyocyte loss. This study tested the hypothesis that prevention of cardiomyocyte apoptosis by Postcon is mediated by mitogen-activated protein kinases pathways. Primary cultured neonatal rat cardiomyocytes were exposed to 3 h hypoxia followed by 6 h of reoxygenation. Cardiomyocytes were postconditioned by three cycles each of 5 min reoxygenation and 5 min hypoxia after prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
123
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 41 publications
7
123
0
1
Order By: Relevance
“…Myocardial ischemia/reperfusion has been shown to activate p38/ JNK MAPK, resulting in cardiac injury and cell death, most prominently via apoptosis. In their study using neonatal rat cardiocytes, Sun et al [20] found that hypoxic post-conditioning could inhibit the expression of p38/ JNK MAPK, which reduced the expression of TNF-α and Bax, and conversely that anisomycin, an activator of p38/JNK MAPK, could offset this protection. The level of phosphorylation of p38/JNK was lower in the GIR group than in the R/I, ER and GDR groups.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia/reperfusion has been shown to activate p38/ JNK MAPK, resulting in cardiac injury and cell death, most prominently via apoptosis. In their study using neonatal rat cardiocytes, Sun et al [20] found that hypoxic post-conditioning could inhibit the expression of p38/ JNK MAPK, which reduced the expression of TNF-α and Bax, and conversely that anisomycin, an activator of p38/JNK MAPK, could offset this protection. The level of phosphorylation of p38/JNK was lower in the GIR group than in the R/I, ER and GDR groups.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is important in cardiovascular disease and may contribute to the development and progression of cardiac dysfunction and heart failure (8)(9)(10). In vitro and in vivo studies have suggested a number of potential mechanisms of these adverse effects, including the theory that aldosterone induces apoptosis in myocytes via activation of the calcineurin, p38 MAPK, JNK and ERK1/2 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies provide evidence that aldosterone-mediated myocyte apoptosis is an important component of cardiovascular diseases (9,10). Several mechanisms which may link aldosterone and apoptosis have been suggested, including the activation of the membrane receptor-mediated calcineurin-Bad, c-Jun N-terminal kinase (JNK) and ERK1/2 pathways (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in cardiac physiology have indicated that PostC significantly reduces infarct size and inhibits inflammation and apoptosis [17][18][19][20][21]. Zhao [22] at first documented that PostC reduced infarct size in cerebral I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the protective effect of RPostC against focal cerebral ischemia in rats was also verified [16]. However, its potential protective mechanisms have not been established.Recent developments in cardiac physiology have indicated that PostC significantly reduces infarct size and inhibits inflammation and apoptosis [17][18][19][20][21]. Zhao [22] at first documented that PostC reduced infarct size in cerebral I/R injury.…”
mentioning
confidence: 99%